저위험 산모의 산전 심리사회적 요인과 산후 외 상 후 스트레스 장애 발생과의 관계: 종단적 연구. - 여정희; 박소연 (Journal of Korean Academy of Nursing, 2025)
Purpose: This study aimed to identify prenatal psychosocial factors influencing the development of postpartum post-traumatic stress disorder (PTSD) in both short-term (4-6 weeks postpartum) and long-term (4-6 and 14-18 weeks postpartum) assessments using the wheel model. Methods: This study employed a longitudinal design with 359 women in their third trimester who received care at two maternity hospitals in Busan. Surveys were used to measure depression, anxiety, resilience, and pregnancy-related PTSD during the third trimester (n=318). Postpartum PTSD was assessed at 4-6 weeks (n=198) and at 14-18 weeks postpartum (n=156). Data were analyzed using the t-test, chi-square test, and logistic regression. Results: The prevalence of short-term postpartum PTSD was 32.7%, and that of long-term PTSD was 19.9%. The risk of short-term PTSD increased with higher pregnancy-related PTSD symptoms (odds ratio [OR], 1.04; 95% confidence interval [CI], 1.02-1.07), higher prenatal resilience (OR, 1.09; 95% CI, 1.00-1.18), and lower social support (OR, 0.93; 95% CI, 0.87-0.99). Similarly, the risk of long-term PTSD increased with higher pregnancy-related PTSD (OR, 1.09; 95% CI, 1.04-1.13), higher prenatal resilience (OR, 1.19; 95% CI, 1.06-1.34), and low educational attainment (OR, 6.75; 95% CI, 1.03-44.30). Conclusion: The high prevalence of short- and long-term postpartum PTSD highlights the need for systematic screening and interventions for prenatal factors, including pregnancy-related PTSD, social support, resilience, and education level. Therefore, it is necessary to alleviate pregnancy-related PTSD and strengthen social support during prenatal care to prevent postpartum PTSD. Furthermore, women with high resilience should also be targeted in these interventions, because they can also develop post-partum PTSD.